RESEARCH OF THE PROPERTIES OF COMPRESSED SOFT BIOLOGICAL TISSUES DURING HIGH-FREQUENCY WELDING - Solovyov, V. G.; Lankin, Yu. M.; Romanova, I. Yu. (Medical Informatics and Engineering, 2025)
Background. By means of physical and mathematical modeling to investigate the change in elec- trical and thermophysical properties of soft biological tissues during their compression for a more detailed study of the mechanism of high-frequency welding of such tissues. Materials and methods. Research was conducted on the tissues of pig and calf internal organs, taken no later than three and twelve hours, respectively, after slaughtering the animals. Prior to research, organs were stored at a temperature of +50 C. The following were research: aorta, small intestines, heart muscle, pancreas, liver, lungs. Results. A custom-made dual-frequency bioimpedance analyzer was created for the research. Multiphysical modeling of electrical and thermal processes during welding of the soft biological tis- sues was carried out. The modeling studied the heat distribution with changes in the geometry of the model, which are related to changes in the thickness of the soft biological tissues or the distance between the clamping electrodes. The dynamics of changes in electrical parameters and tempera- ture over time were studied. An analysis of the influence of the power source frequency and heating temperature on the impedance of the model was performed. Conclusions. The main consequence of compression by the electrodes of electrosurgical instru- ments during bipolar high-frequency welding is a significant reduction in tissue thickness even before the electric heating current flows through them. At the pressure levels of the electrodes used during welding, the thickness of fabrics decreases by 5...15 or more times. Further reduction in the thick- ness of the fabrics as a result of their heating by the welding current is much lower and is no more than 10...20 % of the thickness of the fabric at the beginning of its heating. Dehydration of tissues leads to a significant change in their electrophysical properties. Compression of fabrics primarily significantly changes their electrical and thermal conductivity. Comparing the influence of different types of power sources on the soft biological tissues heating temperature allows us to conclude that the use of stabilized power and stabilized current sources is more acceptable due to the smaller influence of the SBT compression ratio on the heating temperature compared to the stabilized volt- age source. Calculations showed that when the model is heated, the impedance first decreases and then increases. Increasing the degree of compression leads to a decrease in impedance and this is observed at different frequencies.